Pioneering Interdisciplinary Academic Field of Digital Humanities in Latvia - Reinsone, Sanita; Platonova, Marina; Smirnova, Tatjana; Seņko, Zane (History of Engineering Sciences and Institutions of Higher Education, 2022)
A mainstream tendency for multimediality of information and exponential growth of data have promoted major changes in the academic paradigm, supporting the transition towards interdisciplinary research-based studies, which has affected the development of the emerging field of Digital Humanities (DH). The paper aims at providing insights into the different activities implemented by the DH community in Latvia, which have contributed to the advancement of the field and stimulated the inclusion of digital research-related courses in the Latvian higher education curricula, reflecting on the establishment and implementation of the Master study programme in Digital Humanities at RTU considering it in its wider Latvian, pan-European, and global context.